Are Family Firms more Tax Aggressive than Non-family Firms? - CHEN, Shuping (Institutional Knowledge at Singapore Management University, 2010)
Taxes represent a significant cost to the firm and shareholders, and it is generally expected that shareholders prefer tax aggressiveness. However, this argument ignores potential non-tax costs that can accompany tax aggressiveness, especially those arising from agency problems. Firms owned/run by founding family members are characterized by a unique agency conflict between dominant and small shareholders. Using multiple measures to capture tax aggressiveness and founding family presence, we find that family firms are less tax aggressive than their non-family counterparts, ceteris paribus. This result suggests that family owners are willing to forgo tax benefits to avoid the non-tax cost of a potential price discount, which can arise from minority shareholders’ concern with family rent-seeking masked by tax avoidance activities [Desai and Dharmapala, 2006. Corporate tax avoidance and high-powered incentives. Journal of Financial Economics 79, 145–179]. Our result is also consistent with family owners being more concerned with the potential penalty and reputation damage from an IRS audit than non-family firms. We obtain similar inferences when using a small sample of tax shelter cases.